The study of fauna and vectorial competency of mosquito (Diptera:Culicidae) at Satu’un Village, Muara Uya Subdistrict, Tabalong District, South Kalimantan Province - Puspawati Tri Baskoro T. Satoto Mahardika A.W (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2011)
In Indonesia, mosquito-transmitted diseases such as malaria, dengue haemorrhagic fever (DHF), and filariasis, stillbecome main public health problems. Mosquito species which usually act as disease vector are Aedes sp, Culex sp,Anopheles sp and Mansonia sp. The aim of this study was to comprehend the mosquito fauna, bionomical and vectorcompetence of Aedes sp, Culex sp, Anopheles sp and Mansonia sp at Santu’un Village, Muara Uya Subdistrict,Tabalong District, South Kalimantan Province. Man Biting method using aspirator was used to capture mosquitoes.Mosquito dissection, ELISA and immunohistochemistry were performed to find microfilaria larvae, sporozoit Sp. ofPlasmodium and dengue virus, respectively. The results showed that Cx.quinquefaciatus, Cx.tritaeniorhyncus, Cxpipiens and Cx.gelidus were exophagic. Culex quinquefaciatus and Cx.tritaeniorhyncus biting activity was began at7 – 8 pm with their biting rate were 102.5 and 44.5 mosquitoes/person/night, respectively. Anopheles umbrosuswas endophagic. Its biting activity peaked at 8 – 9 pm with its biting rate was 0.5 mosquito/person/night. Meanwhile,An. nigerimus and An.kochi were exophagic. The biting activity of An.nigerimus peaked at 8 – 9 pm with its bitingrate was 0.5 mosquito/person/night. Anopheles kochi biting activity peaked at 6 – 7 pm with its biting rate was 1.5mosquito/person/night. Aedes albopictus was found at 6 - 7 pm with its biting rate was 2.5 mosquitoes/person/night.Mansonia bonea was exophagic. Its biting activity peaked at 11 – 12 pm with its biting rate was 2 mosquitoes/person/night. The average temperature and humidity of this study were 26.14 ± 0.30o and 94.60 ± 0.48%,respectively. Culex sp. usually rested inside the house in the morning. The breeding places of mosquitoes werepuddle of water near house, water container, old/unused vehicles, footprint, and water tank. The water temperatureof the breeding place was 25 oC. Its pH was 5.6 with 0 per mil salinity. This study did not found the vector ofmalaria, DHF, and filariasis. In conclusion, four genera of mosquitoes i.e. Culex, Anopheles, Aedes and Mansoniawere found at Santu’un Village. However, vectors of malaria, DHF and filariasis were not found at this village.Key words : Culex - Anopheles - Aedes – Mansonia - fauna - vector